TikTok turned Bailão? The Dissemination of Funk on the TikTok Platform - Letícia Prior Breda (2022)
This article seeks to analyze the spreading of funk through the TikTok platform. In order to understand the dynamics of the application and how this resource works as a strategy for the propagation of the musical genre, the multiple case study technique was used, analyzing two songs 'Oh Nanana', by Bonde R300, and 'Tudo no Sigilo', by Vytinho NG feat MC Bianca. The selected songs belong to a May 2020 list from the Rolling Stone Portal, which indicated seven Brazilian songs that, at the time, were viral on TikTok. Of these, two funks were chosen. The results obtained point to the relevance of the platform for the propagation of funk in the country. The platform affordances combine editing features, music, choreography and challenges as a way to facilitate the production of creative content by individuals. These materialities are responsible for facilitating connectivity/engagement practices that serve as a strategy to propagate music on TikTok.